Exploring forecast-based management strategies for stormwater detention ponds. Issue 8 (16th November 2016) - Gaborit, E.; Anctil, F.; Pelletier, G.; Vanrolleghem, P.A.
Abstract : Dry detention ponds are commonly implemented to mitigate the impacts of urban runoff on receiving water bodies. They currently rely on static control through a fixed limitation of their maximum outflow rate. This study investigated the performance of several enhanced management strategies for a dry detention pond located at the outlet of a small urban catchment near Québec City, Canada. Among the enhanced scenarios studied are some previously developed real-time control (RTC) strategies, and new operating rules relying on a daily manual adjustment of the outlet gate. Both types of control make use of rainfall forecasts originating from the initial or downscaled Canadian global ensemble prediction system. Different ways of using the forecasts' ensemble spread were considered to take action. The pond performances were investigated considering three different volumetric capacities (including the existing volume). The RTC scenarios are very promising. The value of taking rainfall forecasts into account to prevent pond overflowing is demonstrated. Strategies involving only manual adjustments on a daily basis do not seem helpful.